Influence of malt on the xanthohumol and isoxanthohumol behavior in pale and dark beers: A micro-scale approach - Paulo J Magalhaes (2011)
The main objective of this work was to understand which compounds are responsible for the partial inhibition of xanthohumol (XN) thermal isomerization during wort boiling of dark malts. With such purpose, worts from different kinds of malt (pale, caramel and roasted) were chemically characterized (e.g. antioxidant activity, polyphenols and melanoidins contents) and studied by several chromatographic techniques. Molecular exclusion chromatography experiments showed that adsorption of XN to polyvinylpolypyrrolidone is lower for the high molecular weight fractions. It seems likely that this is due to the reaction between XN and coloured substances that changes chemical properties of XN or, at least, results in the formation of complexes that have different chemical properties. This leads to an inhibition of XN isomerization observed in this work. It was also verified that the melanoidins content was significantly higher in the higher molecular weight fractions, suggesting that probably these compounds are the main responsible for the XN isomerization inhibiting effect.